Closed-Loop Basal Insulin Delivery Over 36 Hours in Adolescents With Type 1 Diabetes: Randomized clinical trial - Elleri, Daniela (American Diabetes Association, 2013)
OBJECTIVE: We evaluated the safety and efficacy of closed-loop basal insulin delivery during sleep and after regular meals and unannounced periods of exercise. RESEARCH DESIGN AND METHODS: Twelve adolescents with type 1 diabetes (five males; mean age 15.0 [SD 1.4] years; HbA(1c) 7.9 [0.7]%; BMI 21.4 [2.6] kg/m(2)) were studied at a clinical research facility on two occasions and received, in random order, either closed-loop basal insulin delivery or conventional pump therapy for 36 h. During closed-loop insulin delivery, pump basal rates were adjusted every 15 min according to a model predictive control algorithm informed by subcutaneous sensor glucose levels. During control visits, subjects’ standard infusion rates were applied. Prandial insulin boluses were given before main meals (50–80 g carbohydrates) but not before snacks (15–30 g carbohydrates). Subjects undertook moderate-intensity exercise, not announced to the algorithm, on a stationary bicycle at a 140 bpm heart rate in the morning (40 min) and afternoon (20 min). Primary outcome was time when plasma glucose was in the target range (71–180 mg/dL). RESULTS: Closed-loop basal insulin delivery increased percentage time when glucose was in the target range (median 84% [interquartile range 78–88%] vs. 49% [26–79%], P = 0.02) and reduced mean plasma glucose levels (128 [19] vs. 165 [55] mg/dL, P = 0.02). Plasma glucose levels were in the target range 100% of the time on 17 of 24 nights during closed-loop insulin delivery. Hypoglycemia occurred on 10 occasions during control visits and 9 occasions during closed-loop delivery (5 episodes were exercise related, and 4 occurred within 2.5 h of prandial bolus). CONCLUSIONS: Day-and-night closed-loop basal insulin delivery can improve glucose control in adolescents. However, unannounced moderate-intensity exercise and excessive prandial boluses pose challenges to hypoglycemia-free closed-loop basal insulin delivery.